An empirical investigation of IPO pricing and operating performance of firms. - Tan, Michelle Mei Xuan. (2008)
To investigate the relation between firm's intended use of IPO proceeds and underpricing decision. In addition, we investigate if firm's intended use of IPO proceeds will affect long run performance.